SEMANTIC ROLE OF THE NAFRI LANGUAGE VERBS - Antonius Maturbongs (Metalingua: Jurnal Penelitian Bahasa, 2015)
THE Nafri language is one of the languages spoken in Jayapura City of PapuaProvince with a moderate number of speakers. This writing describes semanticroles in Nafri language (Nl), namely verbs of state, verbs of action, and verbs ofprocess. The data was analyzed using qualitative and descriptive methods. Theresults showed that the semantic role of the verbs of state tended to feature thestate of physics and that of mind. The semantic roles of the verbs of actionrepresented the nature of actions, occurences, and movements. Meanwhile, thatof the verbs of process presented the regularity of movements and the regularityof events. The semantic roles of those three verbs showed an interesting implicationthat is an inherent correlation between the valencies of the verbs of state, theverbs of action, and the verbs of process mainly on the first exponent.